Respiratory influence on left atrial volume calculation with 3D-echocardiography. Issue 1 (December 2015) - Sørgaard, Mathias; Linde, Jesper; Ismail, Hafsa; Risum, Niels; Kofoed, Klaus; Kühl, Jørgen; Tittle, Benjamin; Nielsen, Walter; Hove, Jens
Abstract Background Left atrial volume (LAV) estimation with 3D echocardiography has been shown to be more accurate than 2D volume calculation. However, little is known about the possible effect of respiratory movements on the accuracy of the measurement. Methods 100 consecutive patients admitted with chest pain were examined with 3D echocardiography and LAV was quantified during inspiratory breath hold, expiratory breath hold and during free breathing. Results Of the 100 patients, only 65 had an echocardiographic window that allowed for 3D echocardiography in the entire respiratory cycle. Mean atrial end diastolic volume was 45.4 ± 14.5 during inspiratory breath hold, 46.4 ± 14.8 during expiratory breath hold and 45.6 ± 14.3 during free respiration. Mean end systolic volume was 17.6 ± 7.8 during inspiratory breath hold, 18.8 ± 8.0 during expiratory breath hold and 18.3 ± 8.0 during free respiration. No significant differences were seen in any of the measured parameters. Conclusions The present study adds to the feasibility of 3D LAV quantitation. LAV estimation by 3D echocardiography may be performed during either end-expiratory or end-inspiratory breath-hold without any significant difference in the calculated volume. Also, the LAV estimation may be performed during free breathing.